CO2-induced low pH in an eastern oyster (Crassostrea virginica) hatchery positively affects reproductive development and larval survival but negatively affects larval shape and size, with no intergenerational linkages: . (25th June 2020) - Clements, Jeff C; Carver, Claire E; Mallet, Martin A; Comeau, Luc A; Mallet, André L
Abstract: In North America, studies regarding effects of CO2 -induced low pH in bivalve aquaculture are largely restricted to the US Pacific coast. Studies on species from the northwest Atlantic are lacking. Furthermore, information on the roles of intergenerational exposure and biological sex in bivalve responses to low pH, particularly in an aquaculture-specific context, is scant. We tested if short-term (1 month) exposure to CO2 -induced reductions in pHNBS affected the reproductive development of male and female eastern oysters ( Crassostrea virginica ) during hatchery-specific reproductive conditioning and whether maternal and/or paternal exposure influenced larval responses. Reduced pH (7.5–7.7) increased the rate of reproductive development in both males and females. There was no indication of intergenerational effects; adult pH conditions did not affect early larval development. In contrast, low pH conditions experienced by gametes during spawning, fertilization, and embryo incubation (48 h) resulted in higher larval survival (+6–8% from control), reduced shell height (−2 to 3 µm), and increased deformities (abnormal shell shape; +3–5%). We suggest that local adaptation to acidic land runoff may account for the positive effects of low pH observed in this study. Bioeconomic assessments are now needed to understand the implications of reduced pH on aquaculture operations in these regions of Atlantic Canada.